MODEL PEMBERDAYAAN MASYARAKAT DESA TEHORU KABUPATEN MALUKU TENGAH (TINJAUAN PROGRAM P3SD) - Maryam Sangadji; Ummi Duwila (Jurnal Cita Ekonomika, 2020)
Through the Village Law Number 6 of 2014, each village is expected to play a role in the framework of strengthening the village socially and economically. This study aims to examine the empowerment programs that have been carried out by the Ministry of Villages in Tehoru Village through basic social service programs. The research objectives were: (1) To determine the process of implementing the basic social service learning center program; (2) to determine the model for strengthening the basic social service learning center program. The analysis was carried out using a qualitative method approach. The results showed (1) The program implementation process was carried out in two stages, namely: program preparation and program implementation. These two stages have not been maximal in involving stakeholders, it seems that those involved are people who are close to the king, (2) The Empowerment Model of physical and non-physical programs is the experience of the community in management so that the construction expected to be a model of strengthening is from the perspective of the village community Tehoru.